Persistent contaminants in adipose fins of returning adult salmonids to the river Tees (UK). (April 2020) - Assunção, Marta G.L.; Ives, Mark; Davison, Phil M.; Barber, Jonathan L.; Moore, Andy; Law, Robin J.
Abstract: We report on concentrations of polybrominated diphenylethers (PBDEs), polychlorinated biphenyls (PCBs), dichlorodiphenyldichloroethylene ( p, p ′-DDE) and hexachlorobenzene (HCB) measured in the adipose fins of returning adult Atlantic salmon ( Salmo salar ) and sea trout ( Salmo trutta ) to the river Tees in the Northeast of England. Overall, higher concentrations of these contaminants were found in sea trout samples, where detected congeners reflected the more widely used commercial formulations, in particular for the PBDEs. Our results suggest that these fish could be bioaccumulating persistent organic pollutants via diet during their migratory routes (North Sea and the Norwegian Sea) and, in addition, some level of re-mobilisation of these compounds could still be occurring in the UK eastern coastal areas. The use of adipose fin of returning salmonids could be further developed as a non-lethal approach to assess whether persistent contaminants are being accumulated during the juvenile to adult phase of salmonids originating from UK rivers. Highlights: Persistent organic pollutants measured in returning salmonids to the river Tees (UK) Adipose fin used for the first time as a non-lethal approach Detected congeners reflected used commercial formulations, mainly for PBDEs. Overall higher concentrations found in sea trout